Relationship between Height and Arm-Span of Elderly Persons in a Rural Area of Ballabgarh, Haryana - Sunanda Gupta; Rakesh Kumar; Mani Kalaivani; Baridalyne Nongkynrih; Shashi Kant; Sanjeev Kumar Gupta (Indian Journal of Medical Specialities)
Background: Progression in age causes gradual loss in height due to degenerative osteoporotic changes in bones and decrease in the disc space. Hence, proxy measures of height are required in elderly persons. Objective: The objective of the study is to study the relationship between height and arm-span of elderly persons. Materials and Methods: This community-based study was conducted in a rural area of Ballabgarh, Haryana, among elderly persons (age ≥60 years). Four hundred and twenty participants were selected by simple random sampling method. House-to-house visits were made. Height and arm-span were measured. Association between height and arm-span was assessed by Pearson's product-moment correlation coefficient and linear regression analysis. Scatter plot was also made to show the association by age and sex. Results: In both sexes and all age groups, arm-span was seen to be more than height. Linear relationship between height and arm-span was observed. There was strong correlation between height and arm-span in both sexes (correlation coefficient = 0.97, P < 0.001 in both sexes). Conclusion: Arm-span can be measured as an alternative to height in elderly population. Arm-span can be used as a substitute for height for calculation of body mass index, creatinine height index, basal energy expenditure, and pulmonary function test.